Rol genes enhance the biosynthesis of antioxidants in Artemisia carvifolia Buch. Issue 1 (December 2016) - Dilshad, Erum; Ismail, Hammad; Haq, Ihsan-ul-; Cusido, Rosa; Palazon, Javier; Ramirez-Estrada, Karla; Mirza, Bushra
Abstract Background The secondary metabolites of theArtemisia genus are well known for their important therapeutic properties. This genus is one of the valuable sources of flavonoids and other polyphenols, but due to the low contents of these important metabolites, there is a need to either enhance their concentration in the original plant or seek alternative sources for them. The aim of the current study was to detect and enhance the yield of antioxidant compounds ofArtemisia carvifolia Buch. HPLC analysis was performed to detect the antioxidants. With the aim of increasing flavonoid content, Rol gene transgenics ofA. carvifolia were established. Two genes of the flavonoid biosynthetic pathway, phenylalanine ammonia-lyase and chalcone synthase, were studied by real time qPCR. Antioxidant potential was determined by performing different antioxidant assays. Results HPLC analysis of wild-typeA. carvifolia revealed the presence of flavonoids such as caffeic acid (30 μg/g DW), quercetin (10 μg/g DW), isoquercetin (400 μg/g DW) and rutin (300 μg/g DW). Compared to the untransformed plants, flavonoid levels increased 1.9–6-fold and 1.6–4-fold inrol B androl C transgenics, respectively. RT qPCR analysis showed a variable expression of the flavonoid biosynthetic genes, including those encoding phenylalanine ammonia-lyase and chalcone synthase, which were found to be relatively more expressed in transformed than wild-type plants, thus correlating with the metabolite concentration. Methanolic extracts of transgenics showed higher antioxidant capacity, reducing power, and protection against free radical-induced DNA damage. Among the transgenic plants, those harboringrol B were slightly more active than therol C- transformants. Conclusion As well as demonstrating the effectiveness ofrol genes in inducing plant secondary metabolism, this study provides insight into the molecular dynamics of the flavonoid accumulation pattern, which correlated with the expression of biosynthetic genes.